The Relationship between Health Factors and Satisfaction and Academic Performance among Al Buraimi University College Students, Oman - Al Khasawneh, Abdul Hadi M. (Indian Journal of Marketing, 2010)
Health is considered to be one of the most important aspects of life, and one of the major factors that influences the individuals' performance. It affects the physical and mental abilities of individuals. An individual needs to maintain a healthy body to be able to perform physical and mental activities. When individuals suffer from diseases, their performance will be degraded in most situations. In general, health can contribute to the human lifestyle. In order for an individual to lead a healthy life, he must adopt healthy habits that can enhance his performance in life. College is seen as a crucial time of transition from school life to the new college environment, where students can incorporate health-related habits to their new lives. The college life is more demanding and causes stress to the students. It also requires more independence, self-control and self-regulation. College students not only face new academic challenges, but they also face psychological challenges in the new environment. Although some researchers (Rawson, Bloomer, and Kendall, 2001) (Angela Banitt, 2002) have studied new challenges that the students face when they start their new lives (e.g. cigarettes smoking, nutrition, sleeping behavior, physical exercise), yet limited attention has been given to the health habits and its relation to students' academic performance. Few researches studied college students and their health habits and its influence on students' satisfaction and academic performance. Some studies (Budd & Preston, 2001) (Pilcher & Walters, 1997) indicate that college students do not adopt healthy habits. Some studies showed that the difficulty in achieving an optimal academic performance is a result of some of their incorrect health habits. (Kelly & Clanton, 2001). If college students are unable to achieve the basic health requirement, they will face physical and mental difficulties during their academic life.